Правові проблеми протидії поширенню деструктивної пропаганди в умовах війни - Коверний, Олександр Євгенійович (Протидія дезінформації в умовах російської агресії проти України: виклики і перспективи: тези доп. учасників міжн. наук.-практ. конф. (Анн-Арбор - Харків, 12-13 груд. 2023 р.), 2023)
The fight against the spread of destructive propaganda in the conditions of war is one of the most difficult and important tasks for any state, since such propaganda can cause significant damage to national security, as well as undermine the trust of the population in the authorities, which as a result can further destabilize the socio-political situation and even contribute to military defeats. Despite the efforts made by the government of our country, Russian propaganda continues to be a serious threat to the national security of Ukraine.